A case study on chemistry classroom practices in the Rwandan secondary schools - Byusa, Edwin; Kampire, Edwige; Mwesigye, Adrian Rwekaza (Heliyon, 2021)
This study aims at assessing the classroom practices of Rwandan chemistry teachers in secondary schools, the second grade (S2), age range between 14 to 16 years old. The classroom observation conducted using the Classroom Observation Protocol for Undergraduate STEM (COPUS). In general, the best practice of group work or collaborative learning and students' engagement was observed. The analysis of the COPUS data reveals that active learning in chemistry classes is dominating, 54% against 42% of passive learning; found high, statistically significant over passive learning at p < .01 (tCritical ¼ 1.89, df ¼ 7, p ¼ .003). The active students' practice is taking 82% of a 2-min time interval across 30 lessons observed, as one class period has 40 min to make 20 intervals of 2 min. Teachers are engaging their students in collaborative learning by assigning them various tasks in groups. These results established the current instructional practices in chemistry classes to draw conclusions and recommendations.
Keywords: Chemistry; Classroom practices; COPUS; Instruction; Rwandan schools